2006
DOI: 10.1111/j.1600-0579.2006.00409.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing subjectivity in the evaluation of pre‐clinical dental preparations for fixed prosthodontics using the Kavo PrepAssistant®

Abstract: The evaluation of pre-clinical technical achievement in fixed prosthodontics cannot be objective when using visual examination of dental preparations. This is, however, still the main method used in dental schools. The present study introduces a new method, based on a mathematical formula, to reduce the problem. The idea emerged when using the Kavo PrepAssistant system (software version 1.05). This system is a 3D-scanner with software that can quantify geometrical differences between an instructor and student … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 3 publications
(3 reference statements)
1
44
0
2
Order By: Relevance
“…This is consistent with study by Dewhurst et al in intestinal absorption physiology study in America [17]. Some studies even demonstrated that students studied with CAL need shorter time to reach the learning objectives, achieving better results than students who did not have access to CAL [18,19]. A study done by Govindaraja found that CAL makes undergraduate students understanding better in both theoretical as well practical aspects and helps them fulfill the learning outcomes [20].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This is consistent with study by Dewhurst et al in intestinal absorption physiology study in America [17]. Some studies even demonstrated that students studied with CAL need shorter time to reach the learning objectives, achieving better results than students who did not have access to CAL [18,19]. A study done by Govindaraja found that CAL makes undergraduate students understanding better in both theoretical as well practical aspects and helps them fulfill the learning outcomes [20].…”
Section: Resultssupporting
confidence: 87%
“…Undoubtedly the approach of students will not be the same as that of teachers. There should be consistent feedback from students [25,26]. In this study many students mentioned that CAL cannot provide actual feel of clinical examination of human subject.…”
Section: Resultsmentioning
confidence: 96%
“…Meanwhile, in the computer-aided evaluation systems, such as PREPassistant, 3D data of tooth preparation are obtained for viewing, while the geometric variations are also processed in 2D planes [15] . In this study, the overall distribution of the amount of tissue reduction was obtained by a 3D distance analysis between the prepared and intact tooth.…”
Section: Discussionmentioning
confidence: 99%
“…While some researchers have obtained the taper, tissue reduction and marginal width of the preparation by manual measurement [12][13][14] , the accuracy and repeatability of these measurements are to some extent limited since the geometric form of the preparation is irregular, as well as there are still differences between the surveyors. Recently, computer-aided methods have been developed for objective evaluation of tooth preparation, for example, the PREPassistant system (KAVO Dental GmbH, Germany), developed for pre-clinical training, can analyze the geometric variations in prepared artificial teeth at given points based on image processing [15][16][17] , in addition, Yayoi et al [18] obtained the axial wall taper of the prepared tooth by using a computerized calculation method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation